Alcohol Consumption the Day of Liver Transplantation for Alcohol‐Associated Liver Disease Does Not Affect Long‐Term Survival: A Case‐Control Study. Issue 1 (19th December 2020) - Ursic‐Bedoya, José; Dumortier, Jérôme; Altwegg, Romain; Belkacemi, Mohamed; Vanlemmens, Claire; Dharancy, Sébastien; Besch, Camille; Shili‐Masmoudi, Sarah; Francoz, Claire; Boillot, Olivier; Meszaros, Magdalena; Meunier, Lucy; et al.
Abstract : Alcohol abstinence before liver transplantation (LT) for alcohol‐associated liver disease (ALD) is required for every candidate. Some listed patients might relapse, resulting in LT for patients nonabstinent during the pretransplant period. Long‐term survival outcomes of these patients have never been studied. We sought to determine whether alcohol consumption on the day of the LT influenced long‐term survival after LT. We conducted a retrospective case‐control study among French LT centers. Cases were defined as recipients between January 1995 and December 2007 having positive blood and/or urine alcohol levels the day of LT. Each case was paired with 2 controls corresponding to patients transplanted for ALD during the same trimester. Patients were classified into 3 categories per alcohol consumption: abstainers, occasional or transitory excessive consumers, or patients with a sustained excessive consumption (daily consumption >20‐30 g/day). During the study period, 3052 LTs for ALD were conducted in France. We identified 42 cases paired with 84 controls. Median blood alcohol level was 0.4 g/L (range 0.1‐4.1 g/L) and median urine alcohol level was 0.2 g/L (range 0.1‐2.0 g/L). Median follow‐up period until death or censoring was 12.9 years (CI95% = [12.3; 13.6]). Long‐term survival was not different between the groups. Relapse to any alcohol consumption rate was higher in the case group (59.5%) than in the control group (38.1%, odds ratio 2.44; CI95% = [1.13; 5.27]), but sustained excessive consumption was not significantly different between the groups (33.3% versus 29.8% in case and control groups respectively, χ 2  = 0.68). Rates of recurrent cirrhosis and cirrhosis‐related deaths were more frequent in the case group. Liver transplantation for nonabstinent patients during the immediate pretransplant period does not result in impaired long‐term survival despite higher relapse and recurrent cirrhosis rates.